2000
DOI: 10.1577/1548-8659(2000)129<0487:hubssi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Habitats Used by Shortnose Sturgeon in Two Massachusetts Rivers, with Notes on Estuarine Atlantic Sturgeon: A Hierarchical Approach

Abstract: Biotelemetry of shortnose sturgeon Acipenser brevirostrum and Atlantic sturgeon A. oxyrinchus oxyrinchus was used to study fish uses of habitat in several hierarchical classes in the Connecticut and Merrimack rivers. Hierarchical classes were geomorphological region (straight river run, run with an island, and river curve), river cross section (channel or shoal), and microhabitat (water depth, bottom current, substrate, and illumination). Coastal wandering juvenile Atlantic sturgeon were summer visitors to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 22 publications
(42 reference statements)
2
36
1
Order By: Relevance
“…Because movement occurred during the late summer and fall, it likely reflects a movement of wild juveniles to wintering habitat. Shortnose sturgeon move to wintering areas during the same time period (Kynard et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because movement occurred during the late summer and fall, it likely reflects a movement of wild juveniles to wintering habitat. Shortnose sturgeon move to wintering areas during the same time period (Kynard et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The 10 wintering juveniles spent 67% of the time on sand, not gravel habitat, but the preference was not significant, likely because only 10 fish were tested. Wintering juveniles of six North American sturgeons prefer sand (Parker et al unpublished data), and wintering juvenile (and adult) Connecticut River shortnose sturgeon, A. brevirostrum, use deep, sandy habitat (Kynard et al 2000). Thus, sandy deep-water habitat may be typical winter habitat of many sturgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research of overwintering environments has increased during the last 2 decades, and the habitat and behavior of a large number of freshwater fish have been investigated (Riehle & Griffith 1993, Kynard et al 2000, Huusko et al 2007). However, the overwintering microhabitats of marine and estuarine fishes are mainly unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the safety and efficiency of fish ladders for use by larger species, such as sturgeon, the modification of fish ladders by incorporating orifices into the traditional pool and weir design has been reported and the study of swimming behavior for the gulf sturgeon (Chan et al 1997) and for the wild, shovelnose sturgeon (Hurley et al 1987;Adams et al 1997) have been reported. Identifying attraction speed of flow, passage time, sustained swim speed, hydraulic conditions, and locomotory activity are necessary to consider for the effective design of fishways and passage facilities (Auer 1996;Chan et al 1997;Schaffter 1997;Quist et al 1999;Kynard et al 2000;Bramblett and White 2001;Peak and Farrell 2004;Castro-Santos 2005). White and Mefford (2002) reported that passage was more successful in the rock fishway because a variety of flow velocities were available, and fish seemed to search for the best possible hydraulic conditions.…”
Section: Introductionmentioning
confidence: 99%